Research on the Innovative Path of Rural Grassroots Party Organization Construction Leading the Modernization of Rural Governance - Lu, Xinyong; Chen, Runqi; Guo, Tinghong; Liang, Siyang; Zhang, Ning (International Journal of Social Sciences and Public Administration, 2024)
This article focuses on the role and challenges of rural grassroots party organizations in leading the modernization of rural governance, conducting in-depth research and analysis from aspects such as party organization system construction, inadequate function, and integration with villagers’ self-government organizations. It analyzes the current development status of rural grassroots party organizations and the connotation of the modernization of rural governance, and dissects the problems of inadequate system in party building work, insufficient function of the party organization, and insufficient coordinated development with villagers’ self-government organizations. Based on this, optimization countermeasures such as strengthening system construction, clarifying functional positioning, and promoting the deep integration of party organizations and villagers’ self-government organizations are proposed. It summarizes the significance and practical operation guidance of these countermeasures for improving the role of rural grassroots party organizations in the modernization of rural governance.